Pengembangan Aplikasi My Village sebagai Upaya Mewujudkan Pelayanan Kelurahan yang Prima - Riza Mahdiah; Ari Irawan; Gina Nur Rahmadhaniah; Yasmin Zainab Aqilah; Asky Avia; Sofwatunnisa Sofwatunnisa; Achmad Zacky Bahrudin; Magfirah Damelia Fitri; Mohamad Dodi Noviansyah; Agam Sufiandi (Universitas Indraprasta PGRI Jakarta, 2022)
Village digitization is an important part of efforts to improve the efficiency and effectiveness of services provided in the village. The purpose of this research is to create an application that is in accordance with the characteristics of the village in order to bring order to the archives and databases in the village. As an effort to improve existing services in the village to help the community and provide community satisfaction with services in the village. The method used in this research is a qualitative method, by implementing the system development life cycle system in stages (System Development Life Cycle (SDLC). The main stage consists of Systems Planning, Systems Analysis, System Design, System Selection, Systems Implementation and Systems Maintenance. The data are collected from observation, interviews, and literature studies. The result of this study is My Village application that is used in the administration of the mail service database in the village.